2007
DOI: 10.1007/s11258-007-9365-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking seed dispersal, germination and seedling recruitment in the invasive species Berberis darwinii (Darwin’s barberry)

Abstract: Seedling recruitment is a multi-phased process involving seed production, dispersal, germination, seedling establishment and subsequent survival. Understanding the factors that determine success at each stage of this process is of particular interest to scientists and managers seeking to understand how invasive species spread and persist, and identify critical stages for management. To understand the factors and processes influencing recruitment of the invasive species Berberis darwinii Hook. (Darwin's barberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…No seedlings survived for 2 years at the pine woods environment due to poor initial germination and the thick litter layer that prevented seedling roots from reaching consistently moist soil. In a New Zealand study of invasive Berberis darwinii, McAlpine and Jesson (2007) found similar survival in sunny and shaded locations, but seedlings in the sunny sites performed better overall.…”
Section: Resultsmentioning
confidence: 93%
“…No seedlings survived for 2 years at the pine woods environment due to poor initial germination and the thick litter layer that prevented seedling roots from reaching consistently moist soil. In a New Zealand study of invasive Berberis darwinii, McAlpine and Jesson (2007) found similar survival in sunny and shaded locations, but seedlings in the sunny sites performed better overall.…”
Section: Resultsmentioning
confidence: 93%
“…In New Zealand B. darwinii can become established and persist below the forest canopy (Allen 1991; Allen and Wilson 1992). According to McAlpine and Jesson (2007), seedlings of this species are shade intolerant, while adult plants growing under the canopy come from surviving seedlings with increased shade tolerance. However, although this shrub can grow in both low and high light levels, it achieves higher performance (seedling establishment, total biomass, maximum photosynthesis) in the latter conditions, outperforming even coexisting native species (McAlpine 2005; McAlpine et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The photosynthetic responses of B. darwinii leaves to different light levels and other ecophysiological characteristics have been studied extensively in invaded areas of New Zealand (Allen 1991; Allen and Wilson 1992; McAlpine 2005; McAlpine and Jesson 2007; McAlpine et al 2008). …”
Section: Introductionmentioning
confidence: 99%
“…reduced competition for light, nutrients and moisture) conferred by the lower herbaceous cover at these sites (compared to shrub regrowth), or other factors such as distance from the parent plant; various studies have shown that seedling performance improves with distance from parent plant owing to factors such as reduced levels of competition, disease or predation (e.g. McAlpine and Jesson 2008;Wenny 2000).…”
Section: Native Plantingsmentioning
confidence: 99%
“…Patterns of seed dispersal do not necessarily reflect patterns of seedling establishment, owing to variations in microsite suitability for germination and establishment (Jordano and Herrera 1995;McAlpine and Jesson 2008) and factors such as predation (Wenny 2000). Establishment can be manipulated by altering either site availability or species performance (sensu Pickett et al 1987).…”
Section: Introductionmentioning
confidence: 99%